Promotion academic entrepreneurship thought in bioproducts problem-based learning methodology: a case study - Oliveira, L. (2022)
Entrepreneurship and innovation are priority objectives for the development and increase of economic competitiveness. However, they need a priority intervention and especially directed to activities of a business nature, going beyond the fields of investigation and science. The search for professionals with different skills to overcome the current and foreseen challenges is relevant in the bioproducts sector. Problem-based learning (PBL) is described as an instructional approach, which promotes interdisciplinarity and critical thinking, with the potential to meet current challenges. This article describes a proposal to align the PBL with an innovation program and contest, to be integrated into a master‘s degree in science and technology in bioproducts (MDSTBio) to promote academic entrepreneurship. The alignment of the PBL with the program and contest could allow the development of innovative products with a view to solving problems faced by the bioproducts sector. The PBL strategy could allow students to mobilize knowledge from several curricular units of MDSTBio for the development of different deliverables to participate in the innovation programs and contests. This way, it could be possible to promote innovation in the bioproducts sector, stimulating the entrepreneurial spirit among higher education students, and understand its potential for replication and mobilization of skills acquired in different bioproducts courses.